Evidence for increasing global wheat yield potential. (1st December 2022) - Guarin, Jose Rafael; Martre, Pierre; Ewert, Frank; Webber, Heidi; Dueri, Sibylle; Calderini, Daniel; Reynolds, Matthew; Molero, Gemma; Miralles, Daniel; Garcia, Guillermo; Slafer, Gustavo; Giunta, Francesco; et al.
Abstract: Wheat is the most widely grown food crop, with 761 Mt produced globally in 2020. To meet the expected grain demand by mid-century, wheat breeding strategies must continue to improve upon yield-advancing physiological traits, regardless of climate change impacts. Here, the best performing doubled haploid (DH) crosses with an increased canopy photosynthesis from wheat field experiments in the literature were extrapolated to the global scale with a multi-model ensemble of process-based wheat crop models to estimate global wheat production. The DH field experiments were also used to determine a quantitative relationship between wheat production and solar radiation to estimate genetic yield potential. The multi-model ensemble projected a global annual wheat production of 1050 ± 145 Mt due to the improved canopy photosynthesis, a 37% increase, without expanding cropping area. Achieving this genetic yield potential would meet the lower estimate of the projected grain demand in 2050, albeit with considerable challenges.